2005
DOI: 10.1002/lsm.20258
|View full text |Cite
|
Sign up to set email alerts
|

Urinary calculus fragmentation during Ho: YAG and Er:YAG lithotripsy

Abstract: Background and Objectives: We tested Ho:YAG and Er:YAG laser ablation of human urinary calculi to determine if Er:YAG is a more efficient lithotripsy device. Study Design/Materials and Methods: Ablation efficiency of Ho:YAG and Er:YAG lasers was tested at varying energy settings, ranging from the damage threshold to clinical energy setting associated with Ho:YAG laser. Stones of known composition (calcium oxalate monohydrate (COM), cystine, and uric acid (UA)) were irradiated. Crater width, depth, and ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 43 publications
1
15
1
1
Order By: Relevance
“…In clinical applications, ablation in a liquid environment (e.g. water, blood, saline, or a mixture of them) (IALE) is often encountered when delivering laser radiation through optical fibers for medical applications inside the human body [6]; for example, in arthroscopic surgery [7], orthopedic procedures [8], dentistry [3], osteotomy [4], angioma treatment [9], and urology [10]. However, unlike the case for short-pulse laser ablation, the main mechanism contributing to the promoted ablation performance for long-pulse laser IALE requires further verification.…”
Section: Citationmentioning
confidence: 99%
“…In clinical applications, ablation in a liquid environment (e.g. water, blood, saline, or a mixture of them) (IALE) is often encountered when delivering laser radiation through optical fibers for medical applications inside the human body [6]; for example, in arthroscopic surgery [7], orthopedic procedures [8], dentistry [3], osteotomy [4], angioma treatment [9], and urology [10]. However, unlike the case for short-pulse laser ablation, the main mechanism contributing to the promoted ablation performance for long-pulse laser IALE requires further verification.…”
Section: Citationmentioning
confidence: 99%
“…Experimental studies indicated that Er : YAG laser light (l ¼ 2.94 mm) is more strongly absorbed by urinary calculi than Ho : YAG light and disintegrates stones up to 5 times more efficiently. (5,6,8,9) However, currently available optical fibers do not transmit high energy Er : YAG pulses efficiently because of high absorption of Er : YAG wavelength by OH À group (10). Low-OH silica fibers are highly efficient in transmitting infrared light at wavelengths shorter than 1700 nm.…”
Section: Biophotonicsmentioning
confidence: 99%
“…Erbium:YAG lithotripsy fragments calculi by a photothermal mechanism [10]. Although this lithotripsy mechanism is similar to Holmium:YAG lithotripsy, Erbium:YAG is more efficient than Holmium:YAG lithotripsy [7][8][9]. Erbium:YAG wavelength is highly absorbed by water [11].…”
Section: Figmentioning
confidence: 99%
“…Due to its strong absorption by calculi of multiple compositions, the Erbium:YAG laser has been tested for the next generation lithotripter recently [7][8][9]. The Erbium:YAG laser operates at a wavelength of 2.94 μm and a pulse duration of 250-300 FIG.…”
Section: Introductionmentioning
confidence: 99%